2021
DOI: 10.1155/2021/6692411
|View full text |Cite
|
Sign up to set email alerts
|

Excitability and Threshold Mechanism for Enhanced Neuronal Response Induced by Inhibition Preceding Excitation

Abstract: Postinhibitory facilitation (PIF) of neural firing presents a paradoxical phenomenon that the inhibitory effect induces enhancement instead of reduction of the firing activity, which plays important roles in sound location of the auditory nervous system, awaited theoretical explanations. In the present paper, excitability and threshold mechanism for the PIF phenomenon is presented in the Morris-Lecar model with type I, II, and III excitabilities. Firstly, compared with the purely excitatory stimulations applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…A recent study shows PIF of class-3 neuron, where inhibition preceding excitation can promote the membrane potential to the threshold of action potential, but whether inhibition can induce the PIR spike is unknown. [53] In this study, the PIR spike is identified to be elicited for class-3 excitability that is far from the bifurcation point, which extends the condition for the PIR spikes. This result is consistent with an electrophysiology experiment wherein the PIR spike can be induced in phasic spiking neurons [8] such as caudal mesopallium neurons.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A recent study shows PIF of class-3 neuron, where inhibition preceding excitation can promote the membrane potential to the threshold of action potential, but whether inhibition can induce the PIR spike is unknown. [53] In this study, the PIR spike is identified to be elicited for class-3 excitability that is far from the bifurcation point, which extends the condition for the PIR spikes. This result is consistent with an electrophysiology experiment wherein the PIR spike can be induced in phasic spiking neurons [8] such as caudal mesopallium neurons.…”
Section: Discussionsupporting
confidence: 55%
“…[23,52] Recently, the PIF phenomenon has been simulated for both class-2 excitability and class-3 excitability. [19,53] Compared with class-2 excitability, there are fewer reports about the PIR spike and enhancement of spiking activity induced by the inhibitory effect for class-3 neurons. [7,8] In this study, the effects of an inhibitory autapse with time delay on dynamical behaviors of the Morris-Lecar (ML) neuron with class-3 excitability are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…First, a low-threshold potassium current shown to interact with the synaptic inhibition in MSO and sharpen the temporal sensitivity of the binaural integration ( Khurana et al, 2011 ; Roberts et al, 2013 ; Myoga et al, 2014 ) was omitted. Second, post-inhibitory facilitation that can raise the firing rate under certain conditions ( Beiderbeck et al, 2018 ; Ma et al, 2021 ) and had been observed in the MSO of juvenile mice ( Dodla et al, 2006 ) was also not considered. This phenomenon could possibly compensate for a decreased firing rate induced by the leading contralateral inhibition in MSO.…”
Section: Discussionmentioning
confidence: 99%
“…First, a low-threshold potassium current shown to interact with the synaptic inhibition in MSO and sharpen the temporal sensitivity of the binaural integration (Khurana et al, 2011;Roberts et al, 2013;Myoga et al, 2014) was omitted. Furthermore, post-inhibitory facilitation that can raise the firing rate under certain conditions (Beiderbeck et al, 2018;Ma et al, 2021) and had been observed in the MSO of juvenile mice (Dodla et al, 2006) was also not considered. This phenomenon could possibly compensate for a decreased firing rate induced by the leading contralateral inhibition in MSO.…”
Section: Limitationsmentioning
confidence: 99%